(untitled) (Research, Society and Development, 2022)
Objective: To investigate the aggregation of risk behaviors and the association of chronic non-communicable diseases (NCDs). Methods: This is a cross-sectional study, whose information was collected from the survey of the Surveillance of Risk Factors and Protection for Chronic Diseases by telephone survey (VIGITEL), in the year 2019. The sample consisted of 47,046 individuals between 18 and 95 years old, of both sexes, being 29,507 women and 17,536 men. Those who were not registered with the telephone operators were excluded. The research variables were: demographic and socioeconomic, nutritional status and behaviors, and cardiovascular diseases. For the descriptive analysis of the data, the means ± standard deviation or absolute and relative frequency (n (%)) were formulated in the SPSS 25.0 software. Using the Mplus software, it was possible to verify the subgroups according to the variables. Results: It was observed that the risk factors for heart disease are closely related to current lifestyle habits, involving practicality, physical inactivity and poor diet in nutrients. Conclusion: It is necessary to increasingly promote the practice of physical exercises, the intake of healthy foods, as well as a better quality of life in order to avoid and minimize the risk factors that are related to cardiovascular pathologies.